Age-related response to an acute innate immune challenge in mice: proteomics reveals a telomere maintenance-related cost. Issue 1892 (5th December 2018) - Criscuolo, François; Sorci, Gabriele; Behaim-Delarbre, Margaux; Zahn, Sandrine; Faivre, Bruno; Bertile, Fabrice
Abstract : Ageing is characterized by the impairment of the acute innate immune response and the upregulation of low-grade inflammation, i.e. inflammaging. At the cellular level, telomeres are considered as a marker of biological ageing as their length is progressively eroded in the absence of repair mechanisms. However, the link between telomeres and inflammaging remains underexplored. We aimed to identify proteins that are differentially expressed between age classes in response to an acute inflammatory challenge. We challenged young (two months) and old (12 months) C57BL/6 mice using bacterial lipopolysaccharide (LPS) and measured telomere length and proteomic profiles in splenocytes. In total, 233 out of the 1966 proteins we quantified differed among experimental groups. A hierarchical clustering analysis revealed that nine of those 233 proteins were differently expressed among the experimental groups. Young mice responded to LPS by increasing the expression of proteins involved in the innate immune response, and interestingly, in telomere length maintenance. However, this regulation was impaired at older ages. These results are in agreement with the assumption that the strength of selection declines with age, potentially explaining the maintenance of costly, dysregulated, immune responses at old age. We suggest that the immune response is competing with the telomere maintenance process, highlighting how telomeres reflect the ageing trade-off even in a species where telomere length is not related to lifespan.